-3(x-2)+2x=x+4

Simple and best practice solution for -3(x-2)+2x=x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-2)+2x=x+4 equation:



-3(x-2)+2x=x+4
We move all terms to the left:
-3(x-2)+2x-(x+4)=0
We add all the numbers together, and all the variables
2x-3(x-2)-(x+4)=0
We multiply parentheses
2x-3x-(x+4)+6=0
We get rid of parentheses
2x-3x-x-4+6=0
We add all the numbers together, and all the variables
-2x+2=0
We move all terms containing x to the left, all other terms to the right
-2x=-2
x=-2/-2
x=1

See similar equations:

| (0.04+x/x)=1.5 | | (w-3)^2=2w^2-9w-19 | | (0.4+x/x)=1.5 | | 7/8+x=14 | | (-2+3t)^4=0 | | n+9=27.4/9 | | 37+x+34-4x=873 | | x+3/x+2+x-3/x-2=2x-3/x-1 | | x+1/3=214 | | 4.25xx=38.25 | | n/6-4=2 | | 5-m=2.75 | | n+9=274/9 | | -5u+2(u+4)=2 | | -4y=4y-3 | | y/5+8=29 | | 2x+5(2x+9)=12x+45 | | f-3/4=4 | | 0.16(y-9)+0.08y=0.14-2.1 | | 4x/3x=50 | | 0=36x^2-478x-2463 | | 7/9c=20 | | -6n-7=5 | | 3m^2-9m-30=0 | | -1.5y=-12 | | 2/3x-3=x+18 | | -17r+8=-26 | | 6w+9=126 | | (-(3/2))y=-12 | | 8n+-10=6 | | 5x+6/3=2x-6/5+7 | | x^2+13.5^2=(3x)^2 |

Equations solver categories